Proses stigmatisasi pada pengikut penghayat kepercayaan pelajar Kawruh Jiwo di Kota Surakarta: Kajian teori Stigma Erving Goffmap - Yosafat Hermawan Trinugraha; Ruwanda Saputro; Yuhastina Yuhastina (LP2M Universitas Sarjanawiyata Tamansiswa, 2023)
This research is about the stigmatization that occurs in adherents of the Pelajar Kawruh Jiwo Indigenous Religious in the city of Surakarta. Stigma is given by other religious groups because it is considered different from the way religious rituals are not like most people. This study aims to describe the form of social stigma and the way adherents of the Pelajar Kawruh Jiwo Indigenous Religious belief manage the stigma given by the people of Surakarta city within the framework of Erving Goffman's sigma theory. The research method used in this research is qualitative method with the type of case study research. Data were collected by observation methods, interviews and literature studies. Researchers found that society stigmatizes adherents of Pelajar Kawruh Jjiwo by being considered a freak, considered shamans who lead to negative things, doing meaningless activities and being considered a bad example. Adherents of the Pelajar Kawruh Jiwo Indigenous Religious carry out stigma management by actively participating in community activities and carrying out activities outside the area of residence.